Label free aptasensor for ultrasensitive detection of tobramycin residue in pasteurized cow's milk based on resonance scattering spectra and nanogold catalytic amplification. (15th October 2019) - Yan, Shang; Lai, Xiaoxia; Wang, Yuxian; Ye, Nengsheng; Xiang, Yuhong
Highlights: Ultrasensitive label free aptasensor was developed and successfully used to determine the tobramycin in milk sample. The developed method showed high accuracy, sensitivity, selectivity and stability for the tobramycin detection. The detection limit was down to 0.19 nM. Abstract: TOB aptamer can be adsorbed on the AuNPs surface to form AuNPs-aptamer complexation to prevent AuNPs aggregation in high salt solution. When TOB was added to the AuNPs solution, the aptamer would bind with TOB and depart from the AuNPs surface. The amount of the AuNPs-aptamer complexation depends on the TOB concentration. Different concentration of AuNPs-aptamer can catalyze the reduction reaction of CuSO4 to produce different size Cu2 O particle. The resonance scattering peak intensities are correlated with the Cu2 O size. Large size Cu2 O particle as a resonance scattering spectroscopy probe can remarkable improve the TOB detection sensitivity. We have succeeded to detect the trace TOB in aqueous solutions. The linear range and limit of detection were 0.50–17 nM and 0.19 nM, respectively. This simple and inexpensive method exhibited high sensitivity and selectivity, which was successfully used to detect TOB in milk. The results indicated the accuracy and precision were satisfied.